The Analysis of Pre-Service Student’s Ability to Develop STEM-Based Learning Media Through Physics Learning Media Lectures - Ismet Ismet; Ketang Wiyono; Evelina Astra Patriot; Pegi Melati; May Rani Rizka (Jurnal Pembelajaran Fisika, 2023)
This study aims to analyze the ability of physics education teacher candidates in developing physics learning media in the form of teaching aids. The research method used is descriptive qualitative. This study was carried out at pre-service teacher in the 3rd semester who takes the physics learning media lectures at physics education department. The sample of the study was code A class and code B class totaling 61 people using the saturated sampling technique. The instrument used is an observation sheet by the course lecturer. The indicators for assessing the instructional tool project in this research are 1) conceptual accuracy; 2) ease of use; 3) media aesthetics; 4) the emergence of STEM aspects; 5) environmentally friendly (Go-green) and the utilization of recycled materials. The study result showed that for class A, students' ability to create STEM-based teaching aids has an average value of 79.8, and using used materials is 79.8. Class B tends to understand the concepts of better teaching aids with an average score of 78.9, and the media used is easy to use at 78.7. Through this research, it can be concluded that students' abilities to develop STEM-based learning media has good criteria. In the implementation of the research, the lecture model was used through project-based learning with a STEM approach. The results of this study will provide implications for further research to measure student creativity and communication skills in the development of teaching aids such as physics learning media.Keywords: Learning media, Pre-service student’s ability, STEMDOI: http://dx.doi.org/10.23960/jpf.v11.n2.202305